Meloxicam in combating clinical mastitis: Nanotechnology-driven hope and opportunities - Vaskuri G S Satya Sainaga Jyothi; Chanti Katta Babu; Rahul Kumar; Pankaj Kumar Singh; Dharmendra Kumar Khatri; Shashi Bala Singh; Jitender Madan (Journal of Pharmacy and Bioallied Sciences, 2022)
Mastitis has well-recognized harmful effects on dairy farm profitability. Furthermore, mastitis impairs the milk component synthesizing ability of secretary tissues. Various therapies are available for the treatment of clinical mastitis. Meloxicam exhibits preferential binding to Cyclooxygenase-2 (COX-2) receptor and consequently generates fewer negative gastrointestinal side effects than nonspecific COX inhibitors such as flunixin meglumine and ketoprofen. Toward this end, research efforts directed at understanding the use of meloxicam alone and in combination with other antibiotics to improve milk quality and production. Therefore, in this review, we have highlighted the mechanism, biopharmaceutical challenges, and merits of meloxicam usage in dairy cattle mastitis. In addition, we also presented the integration of artificial neural network, in silico docking, and nanotechnology-driven topical drug delivery cargo as future opportunity for efficient delivery of meloxicam in the management of clinical mastitis.